(untitled) (LACCEI, 2024)
The present investigation aims to incorporate activated carbon filters in the infiltration field of Basic Sanitation Units (UBS) with hydraulic drag to improve the quality of the effluent. For this, two UBS from the La Manzanilla town center were used, in which a prototype was adapted in such a way that it resembles an infiltration field with activated carbon filters and that allows effluent samples to be taken to the laboratory and determine the concentration of substances to then be compared with the LMP established by MINAM. The results show the average removal of the following parameters after passing through the activated carbon filter: 94.95% of total solids in suspension, 79.75% of Biochemical Oxygen Demand (BOD), 82.00% of Chemical Oxygen Demand (COD) , 99.45% oils and fats and 64.50% thermotolerant coliforms. Concluding that this wastewater treatment allows a removal of physicochemical and microbiological substances below the Maximum Permissible Limits (LMP) established by the Ministry of the Environment (MINAM), improving the quality of the effluent, with the exception of the thermotolerant coliform parameter that exceeds the LMP.